The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/926047
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Properties and Inhibition of Key Enzymes Relevant to Type-2 Diabetes and Hypertension by Essential Oils from Black Pepper

Abstract: The antioxidant properties and effect of essential oil of black pepper (Piper guineense) seeds on α-amylase, α-glucosidase (key enzymes linked to type-2 diabetes), and angiotensin-I converting enzyme (ACE) (key enzyme linked to hypertension) were assessed. The essential oil was obtained by hydrodistillation and dried with anhydrous Na2SO4, and the phenolic content, radical [1,1-diphenyl-2 picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) and nitric oxide (NO)] scavenging abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 29 publications
5
37
0
Order By: Relevance
“…Other animal model studies have shown that the major active component d‐limonene has preventive and ameliorating effects on insulin resistance and dyslipidemia (Jing et al, ; Santiago, Jayachitra, Shenbagam, & Nalini, ). These studies suggest that BPEO has the potential to modulate metabolism and thus be used to prevent and treat metabolic diseases (Oboh et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other animal model studies have shown that the major active component d‐limonene has preventive and ameliorating effects on insulin resistance and dyslipidemia (Jing et al, ; Santiago, Jayachitra, Shenbagam, & Nalini, ). These studies suggest that BPEO has the potential to modulate metabolism and thus be used to prevent and treat metabolic diseases (Oboh et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this finding, our results show BPEO influences the regulation of oncogenes in skin cells. Oboh et al (2013) reported that essential oils distilled from a closely related species (Piper guineense) inhibited key enzymes associated with Type 2 diabetes and hypertension. Other animal model studies have shown that the major active component d-limonene has preventive and ameliorating effects on insulin resistance and dyslipidemia (Jing et al, 2013;Santiago, Jayachitra, Shenbagam, & Nalini, 2014).…”
Section: Effects Of Bpeo On Genome-wide Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological studies attributed to the plant include antioxidant and anti-diabetic (Oboh et al, 2013;Etim et al, 2013), hypolipidemic and hypokalaemic (Nwaichi and Igbinobaro, 2012), insecticidal (Adewoyin et al, 2006), anti-microbial (Oyedeji et al, 2005), sedative activity (Tankam and Ito, 2013) and anticonvulsant activity of aqueous extract of its seed (Abila et al, 1993). The acute toxicity study of the oil conducted in our laboratory indicates the LD 50 value of the oil to be 693 mg/kg, i.p.…”
mentioning
confidence: 90%
“…P. guineense found within the same species and geographical area has been reported to vary in their chemical composition, for example, Ekundayo et al (1988) showed myristicin, safrole, sarisan and elemicin as main compounds; Oyedeji et al (2005) reported β-pinene, α-pinene and germacrene-B as major components; Olonisakin et al (2006) indicated β-pinene, D-Limonene, caryophyllene and car-3-ene as most abundant constituents, while Oboh et al (2013) reported β-pinene, α-pinene, 1,8-cineole and γ-terpinene as the major components of the plant fruit essential oil from this Nigerian spp. The variations in chemical constituents of this plant species could contribute to its divergent biological activities and this therefore necessitate evaluating its chemical composition along with pharmacological activities.…”
mentioning
confidence: 99%